please prove the aforementioned question....
Attachments:
![](https://hi-static.z-dn.net/files/d8c/7938fc40c61f8cc290dc740ef36f30bd.jpg)
Answers
Answered by
1
Step-by-step explanation:
Representing, angle Theta as: A
and, angle Phi as: ∅
So, x cosA - y sinA = x cos∅ - y sin∅
★ x cosA - x cos∅ = y sinA - y sin∅
★ x (cosA - cos∅) = y (sinA - sin∅)
★ x [ 2 sin(A + ∅)/2 sin(∅ - A)/2 ] = y [ 2 cos(A + ∅)/2 sin(A - ∅)/2 ]
★ x [ sin(A + ∅)/2 (-sin(A - ∅)/2) ] = y [ cos(A + ∅)/2 sin(A - ∅)/2 ]
★ -x [ sin(A + ∅)/2 ] = y [ cos(A + ∅)/2 ]
★ -x = y [ cot(A + ∅)/2 ]
★ x + y [ cot(A - ∅)/2 ] = 0
Hence, Proved.
- cos C - cos D = 2 sin(C + D)/2 sin(D - C)/2
- sin C - sin D = 2 cos(C + D)/2 sin(C - D)/2
Thanks! ✨
Similar questions
Science,
6 months ago
Social Sciences,
6 months ago
English,
6 months ago
Math,
1 year ago
Chemistry,
1 year ago